Novel Pathway of Heat Shock- Induced Resistance in Tomato - Tatsuo Sato; Nur Akbar Arofatullah; Sayuri Tanabata (International Journal of Health Science and Technology, 2020)
High-temperature treatment induces disease resistance in various plants (heat shock-induced resistance; HSIR). The role of heat shock transcriptional factors (Hsfs) was investigated in this paper. Heat shock treatment induced disease resistance and up-regulate gene expression of pathogenesis related protein; PR1a2 at 12 and 24 h after treatment. PR1a2 has putative Hsfs binding site in the upstream area. On the other hand, a heat shock transcription factor HsfA2 up-regulated at 6 h after treatment, which was 6 h earlier than salicylic acid accumulation. This time lag suggested the direct contribution of Hsfs, additionally to salicylic acid pathway in the regulation of HSIR in tomato.